Evaluation of the implementation of the good manufacturing practice for traditional medicine industries in Central Java - Marchaban .; Achmad Fudholi; Bambang Suryadi (Indonesian Journal of Pharmacy, 2004)
The study of the GMP implementation for the traditional medicine industries in Central Java has been performed. The GMP for traditional medicine industry is the guidance how to produce and to manage the quality of the product so that it meets to the quality of design and the quality of conformance. The aim of the study is to evaluate how far the GMP is implemented in the traditional medicine industries in Central Java.The method used of the study was a descriptive evaluative qualitative data collected from several traditional industries namely: M, N, O, P, Q, R and S by assessing the implementation level of the GMP in those industries. The evaluation instrument used was the primary data directly collected by interviewing the directors, the managers and the heads of department, and then followed by visitation to the industries to check the primary data and the actual condition.  The result showed that the evaluation of the GMP implementation for the traditional medicine industries in Central Java reached the score of 86.10% that meant of good category, although the quality control, the selfevaluation, and the documentation aspect had to be ameliorated.Key word : GMP, traditional medicine industries